فى معهد الأنصار ببادنج سيدمبوان سومطرا الشمالية (Max Weber) إدارة تنظيم برنامج تعليم اللغة العربية المبنى على المنظمات البيراقراطية - wahyuni, wahyuni (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2020)
This study discusses the description managementof the organization of the Arabic language education programin Al-ansor Islamic Boarding School, North Sumatra. This pesantren is a learning center for Islamic boarding schools in the city in the wake of its success in integrating traditional and modern pesantren curriculum. in the learning process, this pesantren uses the pesantren learning curriculum, and at other times, the pesantren also develops Arabic language programs that are not included in the learning curriculum.this study aims to describe the organization, and implementation of the Arabic language program management process in the Alanshor pesantren. the researchers used a descriptive qualitative research method, with a type of case study research. the research data is the Arabic language program management in the Alanshor Islamic boarding school. The data sources of this study are the founders of Islamic boarding schools, office buildings, student affairs, and teachers. Data collection techniques are carried out by observation, interviews, and document analysis. the results of this study indicate that the organization, and implementation of Arabic programs in Islamic boarding schools is good and in accordance with the organization management theory pioneered by max weber, he called for the need to rationally administer institutions.and may be implemented in other pesantren to increase students’ interest and ability in learning Arabic.